The history of sexuality, volume 1 eaudiobook An introduction. - Foucault, Michel (Tantor Media, 2016)
Why has there been such an explosion of discussion about sex in the West since the seventeenth century? Here, one of France's greatest intellectuals explores the evolving social, economic, and political forces that have shaped our attitudes toward sex. In a book that is at once controversial and seductive, Michel Foucault describes how we are in the process of making a science of sex which is devoted to the analysis of desire rather than the increase of pleasure.